A method for isolation and reverse transcription of high quality RNA from Piper species - Ganga, M Anandaraj, V A Parthasarathy, K Johnson George, R Sandeep Varma, S (Journal of Spices and Aromatic Crops, 2005)
A rapid and efficient protocol for isolation of RNA from Piper leaves is described. RNA was extracted from two Piper species namel y, P. nigrum and P. colubrinulI1, using strong denaturing buffer containing guanidinum thiocyanate and polyvinylpyrollidone followed by p recipitation with pre-cooled sodium acetate and extraction with phenol:chloroform : isoamyl alcohol (25:24:1). RNA was precipitated with isopropanol. The extraction procedure reliably yielded high quality RNA suitable for reverse transcription experiments.